Prayer Poetry in the Conversations of Henrikas Nagys and Liūnė Sutema: From Despair to Salvation - Jakaitė, Dalia (Colloquia, 2021)
The aim of this article is to examine and compare the most noticeable semantic aspects of prayer poetry in the works of Henrikas Nagys and Liūnė Sutema. The classical religious (theological) thought and the modern approach to prayer are important for the concept of prayer. The poetic prayer is more characteristic of Liūnė Sutema than Nagys; this phenomenon leads to a new understanding of the encounter of the two poets in this poetic space. The figures of sister, brother and father, the poetically individual forms of the collective subject (“we”) in the poetry of Nagys and Liūnė Sutema express the significance of the community, which corresponds to the Christian tradition of prayer. The prayer community of both authors share the poetically strong drama of guilt and repentance, truth and error, fidelity and betrayal. The analysis of God as the addressee of prayer revealed a dialogic interpretation of the Bible and the relevance of traditional prayers in the poems of both poets. The wrath of God and its dualism, which takes on the form of antiprayer, and a radical doubt about God’s will is the dominant feature of Nagys’ poetry. God in Liūnė Sutema’s poetry is more personal and is characterized by a paradoxical preservation of tradition. One of the poetically strongest forms of prayer in Liūnė Sutema’s poetry is the variations of “thy will be done” prayer. It is also one of the most suggestive means of a dialogue with Nagys’ poetry.